Resultative and Case in Korean and Mongolian - Kim, Hyun tak (Acta Mongolica, 2006)
It is assumed in Chomsky’s grammar that human beings are biologically endowed with an innate language faculty, which incorporates a set of universal principles which guide the child in acquiring a universal grammar. This language faculty enables the child to develop a grammar of any natural language on the basis of suitable I inguistic experience of the language. However, it cannot be the case that all aspects of the grammar of languages are universal. Although there are universal principles which determine the broad outlines of the grammar of natural languages, there seem to be language particular aspects of grammar children have to learn as part of the task of acquiring their native language. These language particular variations are called parameters of grammar. This leads to the view of language acquisition process that universal principles don’t have to be learned. the child’s syntactic learning task is limited to that of parameter-setting. _ Based on this Principles and Parameters Theory, this paper compares resultative constructions in English, Korean, Mongolian and Japanese and see how different in Case marking of the subject of resultatives in these languages. In section 2, I will review two types of English resultatives and show how the subject of resultatives is Case-marked. In section 3. I will compare Korean and Japanese resultatives and see how different those languages are from English. Section 4 deals with Mongolian resultive constructions and shows that they behave like English in the Case-marking of the subject of resultative constructions. In section 5, I conclude this paper.